Scaling solutions and weak gravity in dark energy with energy and momentum couplings - Amendola, Luca; Tsujikawa, Shinji (Journal of cosmology and astroparticle physics, 2020)
We argue that the ΛCDM tensions of the Hubble-Lemaȋtre expansion rate H0 and the clustering normalization σ8 can be eased, at least in principle, by considering an interaction between dark energy and dark matter in such a way to induce a small and positive early effective equation of state and a weaker gravity. For a dark energy scalar field ϕ interacting with dark matter through an exchange of both energy and momentum, we derive a general form of the Lagrangian allowing for the presence of scaling solutions. In a subclass of such interacting theories, we show the existence of a scaling ϕ-matter-dominated-era (ϕMDE) which can potentially alleviate the H0 tension by generating an effective high-redshift equation of state. We also study the evolution of perturbations for a model with ϕMDE followed by cosmic acceleration and find that the effective gravitational coupling relevant to the linear growth of large-scale structures can be smaller than the Newton gravitational constant G at low redshifts. The momentum exchange between dark energy and dark matter plays a crucial role for realizing weak gravity, while the energy transfer is also required for the existence of ϕMDE.
Gesehen am 01.09.2020